Adaptation of Community Business Entrepreneurs to the COVID19 Pandemic: A Case Study of Adventure Rafting Tourism on the Khek River - Jammor, Siriporn; Pampasit, Rudklaw (MBA-KKU Journal, 2026)
This study aims to investigate the impact of the COVID-19 pandemic and the adaptation strategies of rafting business entrepreneurs on the Khek River. This study adopted a qualitative research approach through in-depth interviews with nine rafting business operators. The findings revealed that the COVID-19 pandemic generated both positive and negative impacts. On the positive side, entrepreneurs became more prepared in planning and managing business risks, while the natural sites had opportunities to recover due to the suspension of tourism activities. On the negative side, the pandemic resulted in decreased income, business closures, loss of local employment opportunities, and increased expenses related to COVID-19 prevention measures. Regarding adaptation strategies, five main strategies were identified: 1) financial adaptation through promotional campaigns and accommodation package deals, 2) personnel adaptation by encouraging employees to engage in supplementary professions, 3) organizational adaptation through service adjustment and organizational downsizing, 4) technological adaptation through online business promotion, and 5) environmental adaptation through tourism conservation activities and landscape improvement. To address future pandemic-related risks, three adaptation approaches are proposed: 1) strengthening business networks, 2) improving the operational readiness of rafting tourism businesses through standardized pricing and service quality, and 3) enhancing entrepreneurs’ technological skills.